Analysis of Layout Design Discrepancies Generated in the Proofreading Process for Product Quality Improvement in the Label & Packaging Manufacturing Industry: Evidence from XYZ Company - Fahri Fadilah Fajar; Maulana Ainul Yaqin; Salsabila Syifa Nuraini; Trisna Trisna; Yudi Prastyo (Lentera Ilmu Nusantara, 2025)
PT XYZ Packaging Indonesia is a company that produces various types of packaging for the garment industry, such as labels, stickers, printed labels, and related accessories, with integrated services from concept to execution. This research analyzes design layout discrepancies in the proofreading process, including content shifts, color errors, text format, cutting lines, fonts, as well as barcode and style/PO mismatches, which impact increased rejections, potential customer complaints, and production losses. In the last three months, the company recorded an average proofreading defect of 15%, mainly due to content errors of 10%. Using the PDCA method, the research identified root causes such as the absence of visual inspection standards, inconsistent work instructions, high workload, and suboptimal digital proofing. Through PDCA, improvements were implemented including standard checklists, two-step verification, increased operator training, and integration of automatic preflight software which reduced proofreading errors to 0%. These results confirm that PDCA effectively improves design layout accuracy and reduces rejects, as well as highlighting the importance of prepress-based quality control in the label and packaging industry.